Utilization of autogenous bone, bioactive glasses, and calcium phosphate cement in surgical mandibular bone defects in Cebus apella monkeys - Cancian, D. C. J.; Vieira, Eduardo Hochuli [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Garcia, I. R. (Quintessence Publishing Co Inc, 2004)
Purpose: the purpose of the present study was to evaluate the histologic results of bone cavities that were surgically created in the mandibles of Cebus apella monkeys and filled with autogenous bone, PerioGlas, FillerBone, or Bone Source. Materials and Methods: Surgical cavities 5 mm in diameter were prepared through both mandibular cortices in the mandibular angle region. The cavities were randomly filled, and the animals were divided into groups according to the material employed: Group 1 cavities were filled with autogenous corticocancellous bone; group 2 cavities were filled with calcium phosphate cement (BoneSource); and group 3 and group 4 cavities were filled with bioactive glass (FillerBone and PerioGlas, respectively). After 180 days the animals were sacrificed, and specimens were prepared following routine laboratory procedures for hematoxylin/eosin staining and histologic evaluation. Results: the histologic analysis showed that autogenous bone allowed total repair of the bone defects; bioactive glasses (FillerBone and PerioGlas) allowed total repair of the defects with intimate contact of the remaining granules and newly formed bone; and the cavities filled with calcium phosphate cement (BoneSource) were generally filled by connective fibrous tissue, and the material was almost totally resorbed. Discussion: the autogenous bone, FillerBone, and PerioGlas provided results similar to those in the current literature, showing that autogenous bone is the best Choice for filling critical-size defects. Synthetic implanted materials demonstrated biocompatibility, but the bioglasses demonstrated osteoconductive activity that did not occur with calcium phosphate (BoneSource). Conclusion: According to the methodology used in this study, it can be concluded that the utilization of autogenous bone and bioactive glasses permitted the repair of surgically created critical-size defects by newly formed bone; the synthetic implanted materials demonstrated biocompatibility, and the bioactive glasses demonstrated osteoconductive activity. The PerioGlas was mostly resorbed and replaced by bone and the remaining granules were in close contact with bone; the FillerBone showed many granules in contact with the newly formed bone; BoneSource did not permit repair of the critical-size defects, and the defects were generally filled by connective fibrous tissue.
Keywords: bioactive glass; calcium phosphate cement; osteogenesis